-8x+16=-2(5x-1)

Simple and best practice solution for -8x+16=-2(5x-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8x+16=-2(5x-1) equation:



-8x+16=-2(5x-1)
We move all terms to the left:
-8x+16-(-2(5x-1))=0
We calculate terms in parentheses: -(-2(5x-1)), so:
-2(5x-1)
We multiply parentheses
-10x+2
Back to the equation:
-(-10x+2)
We get rid of parentheses
-8x+10x-2+16=0
We add all the numbers together, and all the variables
2x+14=0
We move all terms containing x to the left, all other terms to the right
2x=-14
x=-14/2
x=-7

See similar equations:

| 7(n+1)=7(n+2) | | 77=1/2h(2+9) | | 4(3x=1)=10 | | 2a+4=3+2 | | 4x+3x+6=24 | | 1/6d+2/3=1/4d-2/8 | | 0.6-0.3p=0.1(p+6) | | 1/y-1+1/y+1=1 | | 4x^2-42x=7x-12 | | (*3)(x/12)=1 | | 4x+9/3+4x=8 | | 6d-5=7 | | -2.4=s-2.6 | | 7(n-2)=7n-2 | | 1/y-1+1/y+1=0 | | 7=-9x-2 | | -9(7k+1)=63 | | 4(3d+2)=22d-2 | | 1/10y+2=6 | | (2x+3)^2=63 | | -5+13x+60=180 | | x=5/9+x+2/2=3 | | 11x-3x+96=11x+51 | | 0.1x-31=90 | | 3.8r=-30.4 | | 0=-0.01x^2+1.22x+3 | | 0.02(4t+8)=0.08(t+1)+0.08 | | 2m+5-6m=75 | | 14(y-6)=7 | | 2+2x–5=5(x+3) | | 9x-3x+99=9x+60 | | 3(2x-3)=35 |

Equations solver categories